Effectiveness Of Inspiratory Muscle Training On Vo₂Max: Literature Review - Ni Putu Ayu Dika Utami (Universitas Negeri Semarang, 2026)
Maximal oxygen uptake (VO₂max) serves as primary indicator of cardiorespiratory capacity among active individuals and athletes. This literature review evaluates effectiveness of inspiratory muscle training (IMT) for enhancing VO₂max and aerobic capacity in healthy/active populations including active children, pre-hypertensive young adults, amateur runners, and artistic athletes. Literature searches conducted across Google Scholar, PEDro, PubMed (2020-2025) using keywords